2018
DOI: 10.3329/jbau.v16i1.36476
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and economics of maize–squash intercropping at different planting systems

Abstract: The competitive behaviors of maize–squash intercropping at different planting systems were studied at Regional Agricultural Research Station, Hathazari, Chittagong, Bangladesh during the Rabi season of 2016–17 to find out the suitable planting arrangement of maize–squash intercropping for maximum productivity and economic return. There were seven treatments i.e. T1= sole maize, T2= 1 row maize (100%) + 1 row squash (6 plants/row), T3= maize paired row (100%) + 1 row squash (5 plants/row), T4= maize paired row … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…This means that in the pattern of two rows of tall plants (maize) and two of low plants (husk tomato adjacent to squash), squash made a greater contribution to species yield. The results are similar to those obtained by Mahmud et al (2018), who showed that intercalating two rows of maize and two rows of squash has the highest land equivalent ratio (1.62), compared with other topological patterns. The lower yield of the MTMS pattern, compared with MMTS and monocrops, is attributed to competition among the species for light, water, and nutrients (Mahmud et al, 2018).…”
Section: Land Equivalent Ratiosupporting
confidence: 89%
See 4 more Smart Citations
“…This means that in the pattern of two rows of tall plants (maize) and two of low plants (husk tomato adjacent to squash), squash made a greater contribution to species yield. The results are similar to those obtained by Mahmud et al (2018), who showed that intercalating two rows of maize and two rows of squash has the highest land equivalent ratio (1.62), compared with other topological patterns. The lower yield of the MTMS pattern, compared with MMTS and monocrops, is attributed to competition among the species for light, water, and nutrients (Mahmud et al, 2018).…”
Section: Land Equivalent Ratiosupporting
confidence: 89%
“…The results are similar to those obtained by Mahmud et al (2018), who showed that intercalating two rows of maize and two rows of squash has the highest land equivalent ratio (1.62), compared with other topological patterns. The lower yield of the MTMS pattern, compared with MMTS and monocrops, is attributed to competition among the species for light, water, and nutrients (Mahmud et al, 2018). Albino-Garduño et al (2015) report similar results for intercalating one row each of maize and beans; the low yields of the short crops are attributed to shading by the maize and the extensive distribution of maize roots.…”
Section: Land Equivalent Ratiosupporting
confidence: 89%
See 3 more Smart Citations